SMART PLATFORM FOR SUPPORT ISSUES AT THE FIRST AND LAST MILE IN THE SUPPLY CHAIN - THE CONCEPT OF THE S-MILE PROJECT - Marcin STANIEK; Grzegorz SIERPIŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The concept of an innovative support tool for freight transport used in planning, organization and realization is presented in this paper. In addition to the basic functions of a fleet management tool, the educative approach towards environmentally friendly behaviour will be based on promoting ecological solutions, such as unconventionally powered cars, e.g., electric vehicles (EVs). The suggested criteria for a routing algorithm, which will be implemented in the freight transport planner tool, not only allows routing in relation to time and cost criteria, but also the criterion regarding the limitation of emissions of harmful factors. The implementation of innovative the S-mile platform gives rise to environmentally friendly cognition behaviour in the freight transport sector. This is a fundamental aspect to its application, which could help to move the planning, organization and realization of freight transport in the direction of more environmental friendly solutions